Mahakal Temple at the entrance of the Bijolia Temple Compex - Temples of India Project Team (Jio Institute, 2024)
The front view of the Mahakal Temple shows that the temple can be reached from the west. It has a small mukhamandapa (front porch) with a flat roof. The entrance to the mukhamandapa is adorned by sculptures of Ganesha and Bhairava on either side.